Crime and Deviant Behaviour of Contemporary Polish Youth (Self-report Study) (Archives of Criminology, 2006)
The latest self-report delinquency study took place in school year 2002/2003 on a national random school sample of 13-16 years old young people. The size of the sample was 3857 persons. The questionnaire contained questions on problem behaviour and offending (property offences, violent offences against persons and objects, computer-related offences, drugs use and selling) as well as questions on school and family situation, friends, leisure time and attitudes.